2014
DOI: 10.1371/journal.pone.0106944
|View full text |Cite
|
Sign up to set email alerts
|

The Phylogeographical Pattern and Conservation of the Chinese Cobra (Naja atra) across Its Range Based on Mitochondrial Control Region Sequences

Abstract: The vulnerable Chinese cobra (Naja atra) ranges from southeastern China south of the Yangtze River to northern Vietnam and Laos. Large mountain ranges and water bodies may influence the pattern of genetic diversity of this species. We sequenced the mitochondrial DNA control region (1029 bp) using 285 individuals collected from 23 localities across the species' range and obtained 18 sequences unique to Taiwan from GenBank for phylogenetic and population analysis. Two distinct clades were identified, one includi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
35
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(38 citation statements)
references
References 39 publications
3
35
0
Order By: Relevance
“…) and Naja atra (Lin et al . ). The data represented here indicated glacial and climatic cycling also played a key role in driving intraspecific differentiation in this species, which was consistent with other studies (Huang et al .…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…) and Naja atra (Lin et al . ). The data represented here indicated glacial and climatic cycling also played a key role in driving intraspecific differentiation in this species, which was consistent with other studies (Huang et al .…”
Section: Discussionmentioning
confidence: 97%
“…; Naja atra : Lin et al . ). For the combined data of cyt.b and ND4, V. stejnegeri showed a similar intersubclade genetic divergence to the montane species Protobothrops jerdonii (Guo et al .…”
Section: Discussionmentioning
confidence: 97%
“…The relationship between environmental conditions and population genetic diversification is well documented in Naja atra, the closest relative of N. kaouthia. The genetic study of Lin, Hua, Qu, Gao, and Ji (2014) revealed three distinct populations of N. atra across East Asia (n = 285) and suggested that lineage diversification was caused by the development of the Nanling and Luoxiao mountain ranges (the ranges run from west to east in southern China and continue north into central China). Wüster and Thorpe (1989), Wüster and Thorpe (1992), and Wüster et al (1995) examined the systematics of the genus Naja in Asia and variation of N. kaouthia across its range, and these studies have formed the basis of subsequent discussions on the evolution of cobras in South-East Asia.…”
mentioning
confidence: 99%
“…DNA was thawed with 200 µL AE buffer in the middle of spin column. Incubation was done at one minute (15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25) o C), then centrifugated at 8000 rpm (1 minute).…”
Section: Dna Extractionmentioning
confidence: 99%
“…Formation of Taiwan Island occurred during the Miocene, thenit was separated from mainland from the southeast coast of mainland China by Taiwan Strait. Climate change during the Pleistocene caused most of the Taiwan Strait to become a landmass, thus providing an opportunity for N. atra to migrate from mainland China [20]. [15] CONCLUSION N. sputatrix from Java is similar to Naja sumatrana and Naja kouthia with 96-97% similarity level.…”
mentioning
confidence: 98%